Efficacy of Mastodinone® for mastalgia correction in preand perimenopausal women - N I Rozhkova; I I Burdina; S B Zapirova; M L Mazo; S P Prokopenko; O E Yakobs (IP Berlin A.V., 2016)
The purpose of the study wasto examine the effectiveness of the drug Mastodynon® for the treatment of mastopathy in pre - and perimenopausal women. Materials and methods. The research was carried out within 12 months. Patient presenting complaints of pain in the breast, passed a comprehensive examination (clinical and Х-ray and/or sonographic) and questionnaires at the first visit and every 6 months. The plant-based drug Mastodynon®. Results. We examined 38 patients aged 45-56 years. Most women in this group for many years were observed due to mastopathy of different forms and degrees of severity. After 6 months after start of treatment with Mastodynon® the majority of patients reported decrease or absence of pain in the breasts, improvement of psycho-emotional condition. The positive effect of various degree was observed in 71.05% of the patients. After 1 year revealed a stabilization of the therapeutic effect of the drug Mastodynon® in 83.3% of cases. Mastodynon® has shown high effectiveness, good tolerability in the treatment of mastopathy in women of pre - and perimenopausal age, it has improved thepatients quality of life.